Storage and analysis of natural resources information in various territories. (November 2020) - Mikhalev, A S; Tynchenko, V S; Kukartsev, V V; Korpacheva, L N; Kukartsev, V A; Rozhkova, A V
Abstract: The article is devoted to the creation of a system of cartographic models of natural resources for a specific territory. The reasons for the inefficient use of natural resource information in modern Russia are described. The place of natural resource mapping in the formation of a natural resource information space is characterized. The task of systematic consideration of natural resources when creating cartographic support for solving the problems of natural resource management and environmental management planning has been set. It is proposed to develop a program for processing images in the GeoTIFF format, intended for the analysis of natural resources. The structure of the program for the planning and management of environmental management is presented. The main functional types of CMRD are outlined: inventory, estimated, forecasted, recommended. The features of their use at various stages of environmental management are identified.